Feeling as A Bullying Victim” Perceptions of Adolescent Female with Thalassemia Major: A Qualitative Study - Nanda Sartika; Allenidekania Allenidekania; Nani Nurhaeni (GLOBAL HEALTH SCIENCE GROUP, 2023)
Adolescent female with thalassemia major disease experience various psychological, emotional, and social behavioral problems that affect their perceptions of being a woman in the future. The purpose of this study was to explore the perceptions of female teenagers with thalassemia major about being woman. This study uses a descriptive phenomenological approach. The method used was in-depth interviews using semi-structured interview guidelines, and data was analyzed using the Colaizzi method. There were 12 participants selected using a purposive sampling technique. The results was based on the theme, fear of ill- treatment, with the sub-themes, fear of bullying from friends and fear of physical violence from men. Adolescent female with thalassemia major in this study experienced bullying both verbally and physically. Verbally, adolescents receive various kinds of negative labels that are often said by their friends. Three teenagers in this study received physical abuse (physical violence) from their friends and their father. Adolescents with this disease experience fear and worry about their future as women, especially with the experience of treatment from those around them.